Human Resource Management on Cloud - Muhaini Othman; Mastura Arif; Mohd Hafizul Afifi Abdullah; Munirah Mohd Yusof; Rozlini Mohamed (JOIV : International Journal on Informatics Visualization, 2017)
iHRMS is a diligent method to replace the traditional employee management system used by small and mid-scale companies and businesses for managing the employee attendance and payroll. Most traditional methods for managing employee lack the capability to capture employee attendance in real time, hence unable to track employees' punctuality. In another point of view, the problem may affect the overall performance of the employees in an organisation. iHRMS has been introduced not only to cater the said problem but to assist in delivering a more accurate payroll system, therefore, enabling an organisation to better manage their finance.